Exercise prescription for patients with non-specific chronic low back pain: a qualitative exploration of decision making in physiotherapy practice. Issue 4 (December 2016) - Stenner, Rob; Swinkels, Annette; Mitchell, Theresa; Palmer, Shea
Abstract: Background: Providing an effective exercise prescription process for patients with non-specific chronic low back pain (NSCLBP) is a challenging task. Emerging research has indicated that partnership in care and shared decision making are important for people with NSCLBP and calls for further investigation into the approaches used to prescribe exercise. Objective: To explore how shared decision making and patient partnership are addressed by physiotherapists in the process of exercise prescription for patients with NSCLBP. Design: A qualitative study using a philosophical hermeneutic approach. Methods: Eight physiotherapists were each observed on three occasions undertaking their usual clinical activities (total n = 24 observations). They conducted brief interviews after each observation and a later in depth semi-structured interview. Iterative hermeneutic strategies were used to interpret the texts and identify the characteristics and processes of exercise prescription for patients with NSCLBP. Findings: The findings revealed how physiotherapy practice often resulted in unequal possibilities for patient participation which were in turn linked to the physiotherapists' assumptions about the patients, clinical orientation, cognitive and decision making processes. Three linked themes emerged: (1) I want them to exercise, (2) which exercise? – the tension between evidence and everyday practice and (3) compliance-orientated more than concordance based. Conclusions: This research, by focusing on a patient-centred approach, makes an important contribution to the body of evidence relating to the management of NSCLBP. It challenges physiotherapists to critically appraise their approaches to the prescription of exercise therapy in order to improve outcomes for these patients.